Visible Spectrophotometric Determination of Ceftriaxone Sodium in Vials - LAKSHMI, K.S.; ILANGO, K.; NITHYA MATHI, N.; BALAJI, S.; KIBE VICTOR WATHUGI, D.; SATISH KUMAR, A.V. (Asian Journal of Chemistry, 2010)
A rapid, sensitive and simple spectrophotometric method is developed for the estimation of ceftriaxone sodium. It is based on the reaction with 3-methyl-2-benzothiazoline hydrazone hydrochloride and ferric chloride to form a green coloured chromogen with the absorption maximum at 628 nm. The colour obeyed Beer’s law in the concentration range of 10-50 μg/mL. When pharmaceutical preparations were analyzed, the results obtained are in good agreement with the labelled amounts.